High‐resolution mapping of the global silicate weathering carbon sink and its long‐term changes. (19th April 2022) - Li, Chaojun; Bai, Xiaoyong; Tan, Qiu; Luo, Guangjie; Wu, Luhua; Chen, Fei; Xi, Huipeng; Luo, Xuling; Ran, Chen; Chen, Huan; Zhang, Sirui; Liu, Min; et al.
Abstract: Climatic and non‐climatic factors affect the chemical weathering of silicate rocks, which in turn affects the CO2 concentration in the atmosphere on a long‐term scale. However, the coupling effects of these factors prevent us from clearly understanding of the global weathering carbon sink of silicate rocks. Here, using the improved first‐order model with correlated factors and non‐parametric methods, we produced spatiotemporal data sets (0.25° × 0.25°) of the global silicate weathering carbon‐sink flux (SCSFα ) under different scenarios (SSPs) in present (1950–2014) and future (2015–2100) periods based on the Global River Chemistry Database and CMIP6 data sets. Then, we analyzed and identified the key regions in space where climatic and non‐climatic factors affect the SCSFα . We found that the total SCSFα was 155.80 ± 90 Tg C yr −1 in present period, which was expected to increase by 18.90 ± 11 Tg C yr −1 (12.13%) by the end of this century. Although the SCSFα in more than half of the world was showing an upward trend, about 43% of the regions were still showing a clear downward trend, especially under the SSP2‐4.5 scenario. Among the main factors related to this, the relative contribution rate of runoff to the global SCSFα was close to 1/3 (32.11%), and the main control regions of runoff and precipitation factors in space accounted for about 49% of the area. There was a significant negative partial correlation between leaf area index and silicate weathering carbon sink flux due to the difference between the vegetation types. We have emphasized quantitative analysis the sensitivity of SCSFα to critical factors on a spatial grid scale, which is valuable for understanding the role of silicate chemical weathering in the global carbon cycle. Abstract : The spatio‐temporal evolution of global silicate weathering carbon‐sink flux (SCSFα ) from 1950 to 2100 is not clear, which prevents us from clearly understanding of the global silicate chemical weathering. We found that the total SCSFα was expected to increase by the end of this century, but about 43% of the regions might show a significant downward trend, especially in the SSP2‐4.5 scenario, which was mainly controlled by runoff and precipitation factors on the spatial grid scale. This is valuable for promoting the understanding of the role of silicate chemical weathering in the global carbon cycle.